Whole-genome sequence and pathogenicity of a fowl adenovirus 5 isolated from ducks with egg drop syndrome in China - Chen, Hao; Li, Meng; Liu, Siyu; Kong, Juan; Li, Dan; Feng, Jiaxun; Xie, Zhixun (Frontiers in Veterinary Science, 2022)
Recently, fowl adenovirus (FAdV) infection has become widespread in poultry in China and may be asymptomatic or associated with clinical and other pathological conditions. In 2017, a severe egg drop syndrome outbreak in breeder ducks (45 weeks old) occurred in eastern Shandong province in China. The egg production rate declined from 93 to 41%, finally increasing to 80% (did not reach complete recovery). The presence of the virus was confirmed by FAdV-5 specific PCR assay, and it was designated strain WHRS. Furthermore, next-generation and Sanger sequencing of genomic fragments yielded a 45,734 bp genome. Phylogenetic analysis showed that the genomic sequence of the WHRS strain was most homologous-(99.95%) to that of the FAdV-5 17/25,702 and 14/24,408 strain, sharing 32.1 53.4% similarity with other FAdV strains in the genus Aviadenovirus. Infected duck embryos died within 3–5 dpi, but no deaths occurred in the infected ducks. Strain WHRS could cause egg drop syndrome in ducks, accompanied by clinical signs similar to those of natural infections. Overall, strain WHRS is lethal to duck embryos and causes egg drop syndrome in breeder ducks.